1986
DOI: 10.1002/star.19860380308
|View full text |Cite
|
Sign up to set email alerts
|

The Conversion of Fructose and Glucose in Acidic Media: Formation of Hydroxymethylfurfural

Abstract: The effects of several variables on the reactions of fructose and glucose in acidic media have been studied at moderate reaction conditions. Glucose gives rise to the reversible formation of oligosaccharides (reversion products). Fructose was dehydrated into mixtures of hydroxymethylfurfural, levulinic acid, and humines. In addition, substantial reversible dimerisation of fructose occurred in acidic aqueous solutions. The dimerisation equilibrium, which is shifted by a decrease in the water concentration, lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
181
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(196 citation statements)
references
References 42 publications
3
181
1
2
Order By: Relevance
“…Antal et al 21 analysed very profoundly the reaction of sugar decomposition in an aqueous solution and they found four groups of products formed in the course: the isomerisation, the dehydration, the fragmentation and the condensation. Van Dam 22 and Cottier 23 showed that the aqueous and nonaqueous processes led to about 37 products. They demonstrated that the reactions carried out in an aqueous medium provoked the degradation of HMF and that the polymerisation occurred in both aqueous and non-aqueous media.…”
Section: Methodsmentioning
confidence: 99%
“…Antal et al 21 analysed very profoundly the reaction of sugar decomposition in an aqueous solution and they found four groups of products formed in the course: the isomerisation, the dehydration, the fragmentation and the condensation. Van Dam 22 and Cottier 23 showed that the aqueous and nonaqueous processes led to about 37 products. They demonstrated that the reactions carried out in an aqueous medium provoked the degradation of HMF and that the polymerisation occurred in both aqueous and non-aqueous media.…”
Section: Methodsmentioning
confidence: 99%
“…[6] The HMF product can also undergo further rehydration to form levulinic acid and formic acid in the presence of water. [63] Previous studies suggested that HMF formation can take place through an open-chain 1,2-enediol mechanism or through fructofuranosyl intermediates. [24,27,64] However, Antal et al showed that the formation of HMF from fructose proceeds via cyclic intermediates, providing evidence such as 1) facile conversion of 2,5-anhydro-dmannose (an intermediate enol in cyclic mechanism) to HMF; 2) facile formation of HMF from the fructose part of sucrose; and 3) lack of carbon-deuterium bond formation in HMF owing to keto-enol tautomerism in the open-chain mechanism when the reaction is carried out in D 2 O.…”
Section: Conversion Of Sugars Into 5-hydroxymethylfurfural (Hmf)mentioning
confidence: 99%
“…For instance, Van Dam et al studied the dehydration of D-fructose using HCl as the catalyst [11]. The presence of certain salts (e.g.…”
Section: Introductionmentioning
confidence: 99%